2006
DOI: 10.1007/s00262-006-0252-5
|View full text |Cite
|
Sign up to set email alerts
|

Superior anti-tumor protection and therapeutic efficacy of vaccination with allogeneic and semiallogeneic dendritic cell/tumor cell fusion hybrids for murine colon adenocarcinoma

Abstract: Cancer immunotherapy by dendritic cell (DC)/tumor cell fusion hybrids (DC/TC hybrids) has been shown to elicit potent anti-tumor effects via the induction of immune responses against multiple tumor-associated antigens. In the present study, we compared the anti-tumor effects of vaccinating Balb/c mice (H-2(d)) with CT26CL25 colon carcinoma cells that had been fused with either syngeneic DCs from Balb/c mice, allogeneic DCs from C57BL/6 mice (H-2(b)) or semiallogeneic DCs from B6D2F1 mice (H-2(b/d)). Preimmuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 46 publications
2
36
1
Order By: Relevance
“…The presence of allogeneic MHC antigens could act as a "danger signal" [27] to enhance protective immunity against tumours; alternatively, the associated rejection response might swamp critical therapeutic priming against a less dominant TAA. Data comparing autologous and allogeneic DC in other vaccination strategies (tumour cell/DC hybrids and intratumoural DC injection), has suggested that allogeneic DC are more effective [11,14,18,28]. Since non-individualised DC are more practical for clinical preparation and delivery, a direct comparison of autologous and allogeneic DC (though matched for the class I allele presenting the therapeutic epitope ie "semi-allogeneic") impacts both on choice of best therapy, and the feasibility of widespread application for patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of allogeneic MHC antigens could act as a "danger signal" [27] to enhance protective immunity against tumours; alternatively, the associated rejection response might swamp critical therapeutic priming against a less dominant TAA. Data comparing autologous and allogeneic DC in other vaccination strategies (tumour cell/DC hybrids and intratumoural DC injection), has suggested that allogeneic DC are more effective [11,14,18,28]. Since non-individualised DC are more practical for clinical preparation and delivery, a direct comparison of autologous and allogeneic DC (though matched for the class I allele presenting the therapeutic epitope ie "semi-allogeneic") impacts both on choice of best therapy, and the feasibility of widespread application for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous or allogeneic HLA-A2+ mature DC were pulsed with HLA-A2-restricted MelanA/MART-1 [27][28][29][30][31][32][33][34][35] (AAGI-GILTV) peptide for 1 h and mixed with PBMC at a 1:10-1:30 ratio in RPMI 1640 supplemented with 2 mM L-glutamine, 1% v/v non essential amino-acids, 1 mM sodium pyruvate, 10 mM HEPES, 20 mM β-mercaptoethanol, and 7.5% FCS. 5 ng/ml IL-7 (R + D systems, Abingdon, UK) was added to cultures from day 1; 30U/ml IL-2 (R + D systems) was added on day 3 only.…”
Section: Human Naïve Cytotoxic T Cell Primingmentioning
confidence: 99%
“…It has been reported that s.c. vaccination with semi-allogeneic F1 DC-tumour cell hybrids shows significant antitumour effects [21,22] but not s.c. vaccination with peptidepulsed semi-allogeneic DC [22,23], even where an artificial foreign antigen was used as a tumour antigen. We have also demonstrated that semi-allogeneic DC can be used for DC-based immunotherapy provided the i.t.…”
Section: Discussionmentioning
confidence: 99%
“…Alloreactive T-cell response to the alloantigens expressed by the injected DC themselves had been expected to provide the injected DC with additional danger signals via costimulatory-related molecules (such as CD40-CD40L signalling [40][41][42]) or bystander production of T-cell growth factors, resulting in enhanced priming of T-cell responses [21]. However, this positive effect of alloantigens in MHC-disparate donor-recipient combinations might only be obtainable in DC-based immunotherapy with DC-tumour hybrids, where fully allogeneic or semi-allogeneic DCtumour cell fusions show enhanced antitumour effects compared with syngeneic DC-tumour cell hybrids [21,38]. However, there are also conflicting reports in which semi-allogeneic DC-tumour cell hybrids, but not fully allogeneic DC, showed an antitumour effect when injected subcutaneously in a therapeutic model, but these effects were impaired by concurrent alloreactivity [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation